2020
DOI: 10.3390/su12083404
|View full text |Cite
|
Sign up to set email alerts
|

Linking Leaders’ Voluntary Workplace Green Behavior and Team Green Innovation: The Mediation Role of Team Green Efficacy

Abstract: Given the increasing significance of green innovation, scholars have identified environment-oriented leader behavior as a key antecedent of green innovation in firms. However, despite the fact that previous studies highlight all kinds of benefits of environment-oriented leaders’ voluntary workplace green behavior (VWGB) in and for firms, little is known about how these leaders’ VWGB could affect a firm team’s green product innovation as well as their process innovation. To narrow this research gap, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 72 publications
2
20
0
Order By: Relevance
“…Hence, this emotional contagion ignites employees’ harmonious environmental passion [ 22 ]. Although limited research has been conducted on employees’ harmonious environmental passion, our results are according with the existing literature that documented positive workplace outcomes as a result of ethical leadership [ 90 ], as well as a positive association between green psychological climate and employees’ harmonious environmental passion [ 91 , 92 ]. Third, we tested and noted a positive and statistically significant indirect effect of green psychological climate mediation of group-level ethical leadership on employees’ environmental commitment.…”
Section: Discussionsupporting
confidence: 86%
“…Hence, this emotional contagion ignites employees’ harmonious environmental passion [ 22 ]. Although limited research has been conducted on employees’ harmonious environmental passion, our results are according with the existing literature that documented positive workplace outcomes as a result of ethical leadership [ 90 ], as well as a positive association between green psychological climate and employees’ harmonious environmental passion [ 91 , 92 ]. Third, we tested and noted a positive and statistically significant indirect effect of green psychological climate mediation of group-level ethical leadership on employees’ environmental commitment.…”
Section: Discussionsupporting
confidence: 86%
“…The third limitation concerns the potential influences of group members on employees’ behavioral outcomes. Since previous studies have indicated that the interactions among team members within a group can exert an impact on a group’ working environment (e.g., Cai et al, 2020 ), we encourage future studies to take group members’ green-related attitudes and behaviors into consideration to further establish our research findings.…”
Section: Discussionmentioning
confidence: 95%
“…Since employees generally work on teams, we suggest that future studies explore the implications of the trickle-down effect on team-level pro-environmental outcomes. For example, when a leader displays a VWGB, he/she tends to highlight collective interests that would encourage team members to work together on environmental issues for the green benefits of the whole team ( Cai et al, 2020 ). Thus, the team’s pro-environmental work behaviors may increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations